The geopolitics of ‘platforms’: the TikTok challenge - Joanne E. Gray (Internet Policy Review)
In the international digital platform market, a handful of US companies enjoy immense cultural, economic and political power. The short form video platform TikTok provides significant competition to these US incumbents but so far policymakers have focused on the geopolitical implications of TikTok. This paper provides a content analysis of government and company sources, issued between April and August 2020, to systematically establish the geopolitics of the TikTok controversy. It is important to identify geopolitical motivations because they can obscure other factors relevant to platform politics, such as the value of competition in a highly concentrated international platform market. The paper concludes by outlining a research agenda for enhancing competition and avoiding the solidification of conventional geopolitical power dynamics in the international digital platform market.